PENGEMBANGAN BAHAN AJAR KOSMOGRAFI BERBASIS AL QURAN UNTUK MENINGKATKAN KECERDASAN SPIRITUAL MAHASISWA - Furqan Ishak Aksa (Universitas Pendidikan Ganesha, 2017)
This research is based on the dryness of spiritual values in cosmography learning in college. This is because of the cosmographic material currently available contains only the cognitive domain. This condition makes cosmographic learning in college unable to make students as a person who glorifies God and pious in accordance with the mandate of Law Number 12 the year 2012. The research and development procedure is done by modifying the Dick and Carey model which is done through 7 stages. The results showed that the acceptance of teaching materials products reached 80, 42%. An important finding of this research is the integration of Quranic verses into teaching material can add the belief of the respondent to God Almighty for the creation of the universe. This makes the student become a person who glorifies God. Although spiritual intelligence is difficult to measure with various instruments, at least the opinions of most respondents, it can be used as a benchmark that learning Al Quran-based cosmography can increase students' confidence in God Almighty.